Raising or Lowering?—A Case Study of Alethic ACQ in Chinese and Southeast Asian Languages - Cheng Gong (Sciendo, 2016)
The present paper proposes a morphological lowering analysis for the structure associated with alethic ACQ, a postverbal morpheme capable of denoting the modality of ability and possibility in Chinese as well as many Southeast Asian languages. Built in the framework of distributed morphology, we suggest that ACQ is base-generated in a preverbal node as a modal element and lowers to a postverbal position during its derivation on the PF branch. We compare and contrast the proposed lowering account with the other model of analysis, the raising analysis, and demonstrate that the lowering account is superior both conceptually and empirically.